A Double Diffusive Unsteady MHD Convective Flow Past a Flat Porous Plate Moving through a Binary Mixture with Suction or Injection. (26th October 2013) - Sastry, D. R. V. S. R. K.; Murti, A. S. N.
Abstract : The problem of unsteady magnetohydrodynamic convective flow with radiation and chemical reaction past a flat porous plate moving through a binary mixture in an optically thin environment is considered. The governing boundary layer equations are converted to nonlinear ordinary differential equations by similarity transformation and then solved numerically by MATLAB "bvp4c" routine. The velocity, temperature, and concentration profiles are presented graphically for various values of the material parameters. Also a numerical data for the local skin friction coefficient, the local Nusselt number, and local Sherwood number is presented in tabular forms.